Modeling and Fuzzy Control of Modern Refrigeration System - Afzali, Sayyed Hesam Pour (2014)
A Master of Science thesis in Mechatronics Engineering by Sayyed Hesam Pour Afzali entitled, "Modeling and Fuzzy Control of Modern Refrigeration System," submitted in June 2014. Thesis advisor is Dr. Ali A. Jhemi. Available are both soft and hard copies of the thesis.